5x - 5y = 10
3x - 2y = 2
a.create an equivalent system of equations by replacing one equation with the sum of that equation and a multiple of the other. show the steps to do this. part
Multiply this equation 5x - 5y = 10 by 2 and multiply this equation 3x - 2y = 2 by -5
10x - 10y = 20
-15x + 10y = -10
------------------------add
-5x = 10
b.show that the equivalent system has the same solution as the original system of equations.
-5x = 10
x = -2
Plug in x = -2 into any of those equations above
5(-2) - 5y = 10
- 10 - 5y = 10
-5y = 20
y = - 4
Answer
x = -2 and y = -4